REVIEW STATUS PANEL SURYA DI INDONESIA MENUJU REALISASI KAPASITAS PLTS NASIONAL 6500 MW - Ni Made Neli Lestari; I Nyoman Satya Kumara; Ida Ayu Dwi Giriantari (Program Studi Teknik Elektro UNUD, 2021)
PLTS is a power plant that converts sunlight energy into electricity using photovoltaictechnology. Solar panels play an important role in PLTS, because solar panels capture solar radiationthen convert it into electrical energy. The development of solar panel technology is the key to supportthe development of PLTS. This article reviews about the development of solar panels in Indonesia asan important component to support the development of national solar power plants towards a capacityof 6500 MW by 2025. The review will be carried out on various aspects of solar panels including thenational solar panel industry, solar panels available in the domestic market, and the availability ofvarious panels. Data is obtained from the national panel industry, the PLTS project, the PLTS userassociation, the national EPC, the Ministry of Energy and Mineral Resources, and the national solarpanel vendor. The survey result shows there are 241 panels, both local and foreign production. Panelcapacities vary from 5 Watt to 500 Watt and panel voltages are available from 12 Volt, 24 Volt and 48Volt. Based on the survey, it is also obtained the average of Rp/Wp is Rp.18,853/Wp and the averageof W/m2 is 159,46 W/m2. Increasing solar panel production can be done by providing incentives tosolar panel producers in the form of product purchase guarantees and incentives to develop newfactories. Information regarding the current status of solar panels in Indonesia is expected to be aquick reference for people or institutions that need it, and can be used as an introduction to researchand application of PLTS in Indonesia.